Organoleptic Propertiesof RoastCoffee Bean Based on PostharvestMethods, Temperature,and Time of Roasting - Sri Wulandari; Gusmon Sidik; Odi Andanu; Ita Yustina (Agroindustrial Technology Journal, 2023)
Postharvest methodsand roasting processes cause changes in the biochemical composition, physical structure, and organoleptic attributes of coffee. The purpose of this study was to conduct organoleptic tests on roasted red-picked premium Robusta coffee, based on postharvest methods, roasting temperature, and roasting time to obtain the most preferred roasted coffee beans by the panelists. The research design used the Taguchi design with three factors and three levels, Postharvest methodsfactors (full wash, honey, and natural), roasting temperature (150°C, 175°C, and 200°C), and roasting time (10 minutes, 12.5 minutes and 15 minutes) so that the orthogonal array matrix L9 (33) is obtained. The hedonic test (favorability level) in the organoleptic test form consists of a scale of 1-5 rating on each assessed attribute. The panelists consisted of 64 people who were chosen randomly. Data analysis was performed using one-way ANOVA using IBM SPSS Statistics 22. The difference between the means of each treatment was continued with the DMRT test. Postharvest methods, temperature, and roasting time affected the organoleptic of roasted coffee beans, P value or small sig of 0.05 (p<0.05).The most preferred roasted coffee beans by panelist were honey posthervest method, roasting temperature of175°C, and roasting time of 15 minutes.